Structural determination of materials using electron diffraction - Kho, Eric (Nanyang Technological University, 2021)
Electron diffraction is a rapidly growing crystallography technique that allows researchers to determine the atomic and molecular structures of nano-sized crystals, and thus their properties, which has not been able to be achieved by the previous crystallography methods (i.e. x-ray and neutron crystallography). Therefore, in this simulation, we aim to build a viable implementation framework for electron diffraction at NTU so that it can be widely used. The simulation was carried out by extracting structural information from electron diffraction datasets using Diffraction Integration for Advanced Light Source (DIALS), which is an advanced crystallography software developed in Diamond Light Source (Oxford, UK) that takes diffraction data and relates the intensity to the space group of the crystal. Two datasets were used in the simulation. Firstly, a silicon dataset that comprised of a set of diffraction patterns that were obtained at different angles with a range of 600 rotation angle using a transmission electron microscope (TEM). Secondly, an externally acquired set of diffraction patterns with a rotation angle range of 1200. The results and challenges of the extraction were discussed thoroughly in this report.